Developing, Searching and Moving Sustainable Through Renewable Technologies (Global Journal of Human-Social Science, 2013)
The use of renewable energy sources is a fundamental factor for a possible energy policy in the future. Taking into account the sustainable character of the majority of renewable energy technologies, they are able to preserve resources and to provide security, diversity of energy supply and services, virtually without environmental impact. This paper outlines possible energy savings and better performance achieved by different solar passive strategies (skylights, roof monitors and clerestory roof windows) and element arrangements across the roof in zones of cold to temperate climates. The aim of this work is to find possible design strategies, and to find solutions to provide thermal and luminous comfort in spaces of intermittent use and a poor aspect or orientation. In regions where heating is important during winter months, the use of top-light solar passive strategies for spaces without an equator-facing façade can efficiently reduce energy consumption for heating, lighting and ventilation. Passive solar systems for space heating and cooling, as well as passive cooling techniques when used in combination with conventional systems for heating, cooling, ventilation and lighting, can significantly contribute to the energy saving in the buildings sector, and the thermal behaviour of the dependent on the alternatives and interventions made on the building's shell. Exploitation of renewable energy in buildings and agricultural greenhouses can significantly contribute to energy saving. Promoting innovative renewable applications and reinforcing renewable energy market will contribute to preservation of the ecosystem by reducing emissions at local and global levels and will contribute to the amelioration of environmental conditions by replacing conventional resources with renewable sources that produce no air pollution or greenhouse gases and coexist comfortably with existing urban, agricultural and tourist land uses. Sustainable low-carbon energy scenarios for the new century emphasise the untapped potential of renewable resources. Energy efficiency brings health, productivity, safety, comfort and savings to homeowner, as well as local and global environmental benefits
Keywords: renewable energy sources; technologies; applications; sustainable development